2001
DOI: 10.1001/jama.285.14.1874
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Recommendations to Suspend the Birth Dose of Hepatitis B Virus Vaccine

Abstract: We documented a 35% decrease in hospital nurseries that routinely offered HBV immunization 1 year after the AAP and PHS recommendations were made. Special efforts may be required to make at-birth administration of HBV vaccination universal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 12 publications
1
17
0
1
Order By: Relevance
“…15,16 Although the suspension was lifted at the end of 1999, when manufacturers had removed thimerosal from most vaccines, including hepatitis B vaccine, the changes in policy statements have been shown to have an impact on newborn hepatitis B vaccine coverage levels. [17][18][19] These policy changes likely contributed to the delay in the resumption of the birth dose in early 2000 found in this study, with the lowest hepatitis B vaccination rates in January (48.5%) and February (67.5%). This is demonstrated by findings in records of infants who were born in January and February in a single hospital (n ϭ 5) of a medical exemption form signed by the parent agreeing to delay HBV vaccination until the infant was 6 months of age because of concerns regarding thimerosal.…”
Section: Discussionmentioning
confidence: 80%
“…15,16 Although the suspension was lifted at the end of 1999, when manufacturers had removed thimerosal from most vaccines, including hepatitis B vaccine, the changes in policy statements have been shown to have an impact on newborn hepatitis B vaccine coverage levels. [17][18][19] These policy changes likely contributed to the delay in the resumption of the birth dose in early 2000 found in this study, with the lowest hepatitis B vaccination rates in January (48.5%) and February (67.5%). This is demonstrated by findings in records of infants who were born in January and February in a single hospital (n ϭ 5) of a medical exemption form signed by the parent agreeing to delay HBV vaccination until the infant was 6 months of age because of concerns regarding thimerosal.…”
Section: Discussionmentioning
confidence: 80%
“…Our findings are consistent with previous reports indicating that 55% of infants received the birth dose before thimerosalrelated changes in birth dose practices and since the availability of thimerosal-free vaccine, rates have increased but not fully rebounded to their previous levels of immunization. [13][14][15] This study shows that most pediatricians are practicing within current recommendations regarding hepatitis B immunization of infants. In the awareness-to-adherence model, Pathman et al 17 showed that in regards to hepatitis B immunization, physicians generally must agree with a recommendation before they adopt it into their practice.…”
Section: Discussionmentioning
confidence: 93%
“…[12][13][14][15][16] Furthermore, the policy change was misinterpreted by some hospitals that even stopped immunizing infants of mothers who were not screened for HBsAg. 13 Our study blends into the literature by identifying factors associated with use of the birth dose and the desired role of pediatricians in establishing hospital policy for perinatal hepatitis B prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, after the suspension of the birth dose of hepatitis B vaccine was lifted because a thimerosal-free formulation became available, Orum and colleagues documented a 35% decrease in hospital nurseries that routinely offered hepatitis B immunization 1 year after the recommendations were made. 21 Similarly discouraged physicians could create a hole in the public health infrastructure, reducing availability and potentially re-ducing vaccine coverage for years to come.…”
Section: Flu Vaccine Shor Tag E a Nd R Epe At Im Muniz At Ion R At Esmentioning
confidence: 99%